Characterisation of Potential Antidiabetic-Related Proteins from Pleurotus pulmonarius (Fr.) Quél. (Grey Oyster Mushroom) by MALDI-TOF/TOF Mass Spectrometry. (27th August 2014) - Wahab, Nurul Azwa Abd.; Abdullah, Noorlidah; Aminudin, Norhaniza
Abstract : Pleurotus pulmonarius has been reported to have a potent remedial effect on diabetic property and considered to be an alternative for type 2 diabetes mellitus treatment. This study aimed to investigate the antidiabetic properties of ammonium sulphate precipitated protein fractions from P. pulmonarius basidiocarps. Preliminary results demonstrated that 30% (NH4 )2 SO4 precipitated fraction (F30) inhibited Saccharomyces cerevisiae α-glucosidase activity (24.18%), and 100% (NH4 )2 SO4 precipitated fraction (F100) inhibited porcine pancreatic α-amylase activity (41.80%). Following RP-HPLC purification, peak 3 from F30 fraction demonstrated inhibition towards α-glucosidase at the same time with meagre inhibition towards α-amylase activity. Characterisation of proteins using MALDI-TOF/TOF MS demonstrated the presence of four different proteins, which could be implicated in the regulation of blood glucose level via various mechanisms. Therefore, this study revealed the presence of four antidiabetic-related proteins which are profilin-like protein, glyceraldehyde-3-phosphate dehydrogenase-like protein, trehalose phosphorylase-like (TP-like) protein, and catalase-like protein. Hence, P. pulmonarius basidiocarps have high potential in lowering blood glucose level, reducing insulin resistance and vascular complications.